Perspectives and values of industrial workers : the emergence of socio-economic consciousness amongst Coloured workers in the motor manufacturing industry in the Eastern Cape - Roux, Marianne C.(Marianne Cornelia) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1977.